1974
DOI: 10.1126/science.183.4129.1089
|View full text |Cite
|
Sign up to set email alerts
|

Radioreceptor Assay for 1α,25-Dihydroxyvitamin D 3

Abstract: A competitive protein binding assay with a sensitivity of 80 picograms has been developed for 1alpha,25-dihydroxyvitamin D(3), the hormonal form of vitamin D(3). lalpha,25-Dihydroxyvitamin D(3) displaced tritiated hormone from a cytosol-chromatin receptor preparation isolated from chick small intestine, providing a simple assay for the hormone. The concentration of lalpha, 25-dihydroxyvitamin D(3) in human plasma, as determined by this assay, is approximately 6 nanograms per 100 milliliters; in patients with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
76
1
2

Year Published

1975
1975
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(89 citation statements)
references
References 22 publications
10
76
1
2
Order By: Relevance
“…Some vitamin D may also be associated with the cellular and chylomicron fractions of whole blood. Another protein, in addition to Gc-VDBG, may be involved in the transport of la,25-dihydroxy-vitamin D3, the hormonal form of the vitamin which occurs in very low concentrations (9,22). These observations notwithstanding, the evidence strongly supports the contention that Gc-VDBG plays a primary role in vitamin D transport in vivo.…”
Section: Discussionsupporting
confidence: 61%
“…Some vitamin D may also be associated with the cellular and chylomicron fractions of whole blood. Another protein, in addition to Gc-VDBG, may be involved in the transport of la,25-dihydroxy-vitamin D3, the hormonal form of the vitamin which occurs in very low concentrations (9,22). These observations notwithstanding, the evidence strongly supports the contention that Gc-VDBG plays a primary role in vitamin D transport in vivo.…”
Section: Discussionsupporting
confidence: 61%
“…This is about 0.1% of the amount of radioactivity actually present in each intact rat plasma or intestinal sample (4100,000 dpm; see Fig. 1 (7)(8)(9)(10)(11)(12). It should also be kept in mind that both laboratories involved in the Lambert et aL study (6) previously reported plasma 1,25(OH)2D3 levels to be undetectable in anephric subjects (10,12 (6) should be interpreted cautiously because of the points raised above and because of contrary evidence from groups using diverse techniques (2-5, 7-12, 27).…”
Section: Gray Et Al (5) Administeredmentioning
confidence: 99%
“…The authors concluded that 1,25(OH)2D3 was present in the plasma of anephric subjects. However, other investigators, using radioreceptor, radioimmune, and biological assays for 1,25(OH)2D3, have been unable to detect 1,25(OH)2D3 in anephric persons (7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Specific, cytosolic binding proteins for 1 ,25-(OH)2-Da exist in the established target organs, e.g., intestine [ 1,2] and bone [3], as well as in other tissues [4-81, and these 'receptors' appear to transfer the hormone to the nucleus. A similar binding protein was detected in cytosol prepared from rat [9] and mouse skin [lo] suggesting the presence of a cutaneous 1 ,25-(OH)z-D,-receptor system.…”
Section: Introductionmentioning
confidence: 99%